Peran Guru BK Dalam Membantu Menyelesaikan Masalah Prestasi Belajar Siswa di SMP 1 Ulujami Kabupaten Pemalang - Nur Laeli; Muhammad Rifa’i Subhi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
At Ulujami 1 Middle School in Pemalang Regency, student learning achievement is still low. There are several students whose achievements are below average. Through personal counseling services, the ten students are guided by a guidance and counseling teacher. The question is, how can guidance and counseling teachers help students excel at school? The aim of this research is to learn more about how guidance and counseling teachers can help students achieve better emotional learning outcomes. This research uses a qualitative approach with a descriptive design, specifically a field study with the aim of writing from individuals who have determined descriptions of field phenomena. Data and information in the form of narratives are obtained from observations, interviews and triangulation-based documentation as data validity in this kind of research report method. The findings of this research lead to the following conclusions: First, how guidance and counseling teachers can use personal counseling guidance services to improve student learning achievement. in providing group guidance services, especially the Guidance and Guidance Teacher carries out assessments and collaborates with related parties. Prepare an RPL-based program, as well as the necessary facilities and infrastructure. Second, by using the skills that students already have, guidance and counseling teachers are able to encourage low achieving students through individual guidance.